A Continuous 13.3-Ka Paleoseismic Record Constrains Major Earthquake Recurrence in the Longmen Shan Collision Zone - Shi, Wei; Jiang, Hanchao; Alsop, G. Ian; Wu, Guo (Frontiers in Earth Science, 2022)
The thrust collision zone with a low slip rate along the plate boundary is the main stress accumulation area and prone to occur more destructive earthquakes with a longer recurrence interval. Such region is often classified as low seismic risk if lack of continuous records of large earthquakes, such as the eastern Tibetan Plateau before the 2008 Mw 7.9 Wenchuan earthquake. Here, we provide a continuous seismic record in the Longmen Shan thrust fault zone spanning 13000 years based on detailed investigation of the soft-sediment deformation structures and seismites in the Lixian lacustrine sequence. The recurrence time of large earthquakes (M ≥ 8.1) is 1200 years, which is significantly shorter than the previous estimate of 2000-6000 years. The Maoxian-Wenchuan fault is the main fault that triggered the deformation in the Lixian lacustrine sediments. In addition, the frequency of earthquake recurrence in the warm period is more frequent than that in the cold period, which should arouse our attention on the seismic study in the tectonically active regions.